A simplified spin and gradient echo approach for brain tumor perfusion imaging. Issue 1 (5th March 2015) - Stokes, Ashley M.; Quarles, C. Chad
Abstract : Purpose: In this study, we propose a simplified acquisition and analysis approach for spin and gradient echo (SAGE)‐based dynamic susceptibility‐contrast MRI (DSC‐MRI) data that is free of contrast agent T1 leakage effects. Methods: A five‐echo SAGE sequence was used to acquire DSC‐MRI data in rat C6 tumors (n = 7). Nonlinear fitting of all echoes was performed to obtain T1 ‐insensitive ΔR2 * and ΔR2 time series. The simplified approach, which includes two gradient echoes and one spin echo, was also used to analytically compute T1 ‐insensitive ΔR2 * using the two gradient echoes and ΔR2 using all three echoes. The blood flow, blood volume, and vessel size values derived from each method were compared. Results: In all cases, the five‐echo and simplified SAGE ΔR2 * and ΔR2 were in excellent agreement and demonstrated significant T1 leakage correction compared with the uncorrected single‐echo data. The derived hemodynamic parameters for blood volume, blood flow, and vessel size were not significantly different between the two methods. Conclusions: The proposed simplified SAGE technique enables the acquisition of gradient and spin echo DSC‐MRI data corrected for T1 leakage effects yields parameters that are in agreement with the five‐echo SAGE approach and does not require nonlinear fitting to extract ΔR2 * and ΔR2 time series. Magn Reson Med 75:356–362, 2016. © 2015 Wiley Periodicals, Inc.